Modeling of oscillatory processes of viscoelastic plates in a gas flow: Modeling of oscillatory processes of viscoelastic plates in a gas flow - Shamsiddinov, S.; Dodobayev, A.M; Khudayarov, B.A.; Turaev, F.; Gulomov, O.; Khayitov, K. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Let us consider the problem of vibrations of a flexible hereditarily deformable rectangular plate moving in a gas at a high supersonic speed. A plate with sides a and b is flown past on one side by a gas flow. We assume that the flow direction is parallel to side a. We assume that the plate is compressed in the same direction by constant forces 0. We take that the deflections are small compared to the thickness of the plate, and we solve the problem in a linear statement. Taking a linear expression for the aerodynamic pressure and not taking damping into account, we obtain the equation of motion for a plate with the following finite ratio: